Pengaruh Kepemimpinan Transformasional terhadap Kepuasan Kerja Dosen Generasi Z di Perguruan Tinggi Swasta - Monika Sutarsa; Horas Djulius; Yusuf Arifin (Jurnal Ekonomi Bisnis dan Manajemen, 2026)
This study aims to analyze the influence of transformational leadership, motivation, and competence on job satisfaction, as well as their implications for the turnover intention of Gen Z lecturers, with affective commitment serving as a moderating variable. A quantitative approach was employed, utilizing a survey method involving 212 Gen Z lecturers from private higher education institutions in the East Priangan region holding 'B' accreditation. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that transformational leadership, motivation, and competence all have a positive and significant effect on job satisfaction, with coefficients of 0.284, 0.351, and 0.317, respectively. Job satisfaction has a negative and significant effect on turnover intention, with a coefficient of -0.442. Furthermore, transformational leadership, motivation, and competence also exert a significant negative influence on turnover intention. Affective commitment was found to moderate the relationship between job satisfaction and turnover intention, with a coefficient of -0.271. These findings suggest that enhancing leadership quality, motivation, competence, and affective commitment can serve as effective strategies to increase job satisfaction and reduce turnover intention among Gen Z lecturers.